In-Silico Molecular Phylogeny of Philippine Myxomycetes using 18S rRNA and small subunit rRNA (SSU) Gene Sequences: Molecular Phylogeny of Myxomycetes using 18S rRNA and SSU Sequences in the Philippines - Ong, Christian Joseph; Clemente, Richard; Alaijos, Oliver; Pascual, Lady Janine; Aguilar, Russell Neil; Desacula, Raizza (Journal of Tropical Life Science, 2023)
Myxomycetes, commonly called plasmodial slime molds, are eukaryotic organisms usually thriving on terrestrial ecosystems, manifesting attributes of fungi and protists. The current taxonomy of myxomycetes poses serious problems and does not clearly reflect the evolutionary relationships of this group. The literature on myxomycetes in the Philippines has primarily focused on species identification, ecological and diversity studies. However, no attempts have been made yet to elucidate the evolutionary relationships of this class using molecular evidence. The use of 18S rRNA and small subunit rRNA (SSU) sequences in this study to construct phylogenies has revealed that certain taxa, traditionally considered monophyletic, exhibit inconsistencies that warrant further investigation. However, the molecular evidence that supports the division of myxomycetes into two distinct groupings (Lucisporidia and Columellidia) according to spore color remains consistent with the constructed phylogeny using 18S rRNA gene sequences. Therefore, the present study aims to assess Philippine myxomycetes' diversity and evolutionary relationships. In addition, the study aims to compare the conventional taxonomy and molecular phylogeny of myxomycetes species in the Philippines using two molecular barcode markers - the 18S rRNA and SSU sequences. The study demonstrated that it is not always possible for morphology to agree with molecular data. On the other hand, molecular data can be more beneficial in reconstructing phylogenies but only to a certain extent and should be further evaluated.